2015
DOI: 10.1097/md.0000000000001845
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating Positive Expiratory Pressure on Respiratory Resistance in Chronic Obstructive Pulmonary Disease With a Small Amount of Secretion

Abstract: This study aims to evaluate the acute effects of an oscillating positive expiratory pressure device (flutter) on airways resistance in patients with chronic obstructive pulmonary disease (COPD).Randomized crossover study: 15 COPD outpatients from Asthma Lab–Royal Brompton Hospital underwent spirometry, impulse oscillometry (IOS) for respiratory resistance (R) and reactance (X), and fraction exhaled nitric oxide (FeNO) measures.Thirty minutes of flutter exercises: a “flutter-sham” procedure was used as a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 42 publications
2
16
0
17
Order By: Relevance
“…Another study found that short-term use of a Flutter device can reduce airways resistance even in patients with COPD with minimal sputum production. 14 …”
Section: Resultsmentioning
confidence: 99%
“…Another study found that short-term use of a Flutter device can reduce airways resistance even in patients with COPD with minimal sputum production. 14 …”
Section: Resultsmentioning
confidence: 99%
“…There are several reports that alternative types of vibration and oscillation can facilitate air removal and improve lung function in various clinical settings [6][7][8][9][10]. So far, no clinical studies have evaluated the effect of positive vasodilator pressure with Acapella (Smiths Medical Inc, Carlsbad, California) in patients undergoing coronary artery bypass grafting.…”
Section: Introductionmentioning
confidence: 99%
“…The study was powered at 90% to detect a 0.1 kPa L-1 s difference in the primary outcome of trough R5, assuming a within subject standard deviation of 0.13 kPa L-1 s, and an alpha error of 0.05 (two-tailed) [ 19 ]. Students t-tests were used to compare treatment effects at baseline and after chronic dosing.…”
Section: Methodsmentioning
confidence: 99%